Revised extinctions and radii for 1.5 million stars observed by APOGEE, GALAH, and RAVE - Yu, Jie; Khanna, Shourya; Themeßl, Nathalie; Hekker, Saskia; Dréau, Guillaume; Gizon, Laurent; Bi, Shaolan (The astrophysical journal. Supplement series, 2023)
Asteroseismology has become widely accepted as a benchmark for accurate and precise fundamental stellar properties. It can therefore be used to validate and calibrate stellar parameters derived from other approaches. Meanwhile, one can leverage large-volume surveys in photometry, spectroscopy, and astrometry to infer stellar parameters over a wide range of evolutionary stages, independently of asteroseismology. Our pipeline, SEDEX (https://github.com/Jieyu126/SEDEX), compares the spectral energy distribution predicted by the MARCS and BOSZ model spectra with 32 photometric bandpasses, combining data from nine major, large-volume photometric surveys. We restrict the analysis to targets with available spectroscopy from the APOGEE, GALAH, and RAVE surveys to lift the temperature−extinction degeneracy. The cross-survey atmospheric parameter and uncertainty estimates are homogenized with artificial neural networks. Validation of our results with CHARA interferometry, Hubble Space Telescope CALSPEC spectrophotometry, and asteroseismology shows that we achieve high precision and accuracy. We present a catalog of improved interstellar extinction ( 0.14 mag) and stellar radii (σ R /R ≃ 7.4%) for ∼1.5 million stars in the low-to-high-extinction (A V ≲ 6 mag) fields observed by the spectroscopic surveys. We derive global extinctions for 184 Gaia DR2 open clusters and confirm the differential extinction in NGC 6791 and NGC 6819, which have been subject to extensive asteroseismic analysis. Furthermore, we report 36,854 double-lined spectroscopic main-sequence binary candidates. This catalog will be valuable for providing constraints on detailed modeling of stars and for constructing 3D dust maps of the Kepler field, the TESS Continuous Viewing Zones, and the PLATO long-duration observation fields.